Pendampingan BTQ Anak Menggunakan Metode Bernyanyi Berbasis Media Visualisasi Di Korong Simpang Tiga - Zilfadlia Nirmala; Martin Kustati; Rezki Amelia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this assistance is to introduce and provide basic knowledge about hijaiyah letters, both in the form of readings and the basic forms of these letters. This assistance was carried out due to the lack of interest in reading and writing the Qur'an in Korong Simpang Tiga due to the Covid-19 situation and conditions that hit at that time. This assistance is carried out using the Particitpatory Action Research (PAR) method with the initial stage, namely by providing a general description by writing the hijaiyah letter shape on the blackboard, then introducing the reading by singing the song